Careful consideration of the bleeding caused by transbronchial lung cryobiopsies. Issue 5 (21st May 2020) - Bourdin, Arnaud; Romagnoli, Micaela; Gamez, Anne Sophie; Hireche, Kheira; Berthet, Jean Philippe; Mallet, Jean Pierre; Vachier, Isabelle; Nava, Stefano; Reynaud, Paul; Molinari, Nicolas; Suehs, Carey
We read with great interest a research letter by Pannu et al. [1] in the European Respiratory Journal describing unexpected high mortality results in association with transbronchial lung cryobiopsy (TBLC). The team at Vanderbilt University Medical Center has decided to no longer provide TBLC for inpatients with acute diffuse parenchymal lung disease (DPLD) exacerbations, and spotlighted bleeding complications as a predictive factor for a higher risk of mortality for all patients [1]. Lung surface photos show wounds/haemorrhages caused by transbronchial lung cryobiopsy (TBLC). TBLC bleeding can extensively soil airways with consequences for lung function, stressing the need for bleeding prevention and more research via registries. https://bit.ly/34wWAeR